Library Research: An Online Learning at High School as Learning Media - Renny Permata Saputri; Yuliawati Yunus; Monica Fransisca (The Indonesian Journal of Computer Science, 2022)
Technology has begun to applied in the field of education, not only in universities but also in high school. The existence of technology for education encourages the development of learning media, especially online learning. The purpose of this research was to examine implementation of online learning at high school level. The method used is literature review research, which is the research results come from several sources. The data obtained comes from books, research, and articles related to online learning media. Based on the research’s results, it was concluded that the use of online learning media in high school can be applied appropriately and well if it meets certain criteria. The use of online learning as learning media can also directly improved student’s learning outcomes. This statement obtained from research articles related to the topic.